Adjuvant Pitolisant in a Case With Early-Onset Schizophrenia. Issue 6 (November 2021) - Naguy, Ahmed; Pridmore, Saxby; Alamiri, Bibi
Abstract : Objectives: Early-onset schizophrenia is notorious for poor prognostication and treatment refractoriness. Child/adolescent psychiatric population, by virtue of age, is at a heightened risk for cardiometabolic risk of atypical antipsychotics. Available pharmacological options are, sorely, too limited to mitigate this risk. Methods: The authors are reporting here on an adolescent case with early-onset schizophrenia who has favorably responded to olanzapine but with problematic weight gain that failed a trial of add-on metformin. A trial of add-on pitolisant was pursued. Results: Adjunctive pitolisant has successfully helped with the weight issue. Strikingly, there were parallel improvements in both cognitive and negative domains as well. Conclusions: Add-on pitolisant can be a safe and effective strategy to address antipsychotic-induced metabolic syndrome. Gains might also span negative/cognitive domains. This might open new treatment venues for such complicated clinical scenarios that await replication in larger rigorous studies.